A cultural semiotic aesthetic approach for a virtual heritage project: Part A-The semiotic foundations of the approach - Voutounos, Chrysanthos; Lanitis, Andreas (My University, 2016)
This paper presents an integrated framework applied towards the design and evaluation of a virtual museum of Byzantine art that combines the theorized fields of semiotics, virtual heritage (VH), and Byzantine art. A devised semiotic model, the case study semiosphere, synthesizes important principles from the theoretical background justifying the overall design and evaluation methodology. The approach presented has theoretical extensions to the understanding of the role technology plays in promoting a consummatory aesthetic experience for Byzantine art in virtual environments, complementing the experience received from traditional Byzantine art media. Part A of the work presents the development of the semiotic foundation of the study prior to presenting the applied potential of the approach in design and evaluation of VH for Byzantine art, which appears in Part B. The final task of the proposed approach aims to support a meaningful interpretation, assisting in the promotion of the significance (value) of the virtual museum to potential interpreters/visitors.
Keywords: Semiotics; Semiosphere; Aesthetics; Virtual heritage; Byzantine art